Coronavirus Disease 2019 (COVID-19) Pandemic and Pregnancy. Issue 1 (24th March 2021) - Dashraath, P.; Wong, J.L.J; Lim, M.X.K; Lim, L.M.; Li, S.; Biswas, A.; Choolani, M.; Mattar, C.; Su, L.L.
Abstract : ( Am J Obstet Gynecol . 2020;222:521–531) Caring for vulnerable populations is a critical component of pandemic management. Pregnant women are susceptible to respiratory illness with an increased infectious morbidity and mortality. While clinical information is limited on the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on the pregnant population, both the SARS-CoV and MERS-CoV outbreaks of the last 2 decades resulted in approximately one third of infected pregnant women dying from the illness. The purpose of this paper was to summarize the clinical features of coronavirus disease 2019 (COVID-19) in pregnant women, and present a pragmatic and integrated framework for handling complex intricacies involved in disease management.